Heterogeneous formation and light absorption of secondary organic aerosols from acetone photochemical reactions: remarkably enhancing effects of seeds and ammonia - S. Zhang; Y. Gao; X. Xu; L. Chen; C. Wu; C. Wu; Z. Li; R. Li; B. Xiao; X. Liu; R. Li; R. Li; et al. (Atmospheric Chemistry and Physics)
Secondary organic aerosols (SOAs) from highly volatile organic compounds (VOCs) are currently not well represented in numerical models as their heterogeneous formation mechanisms in the atmosphere remain unclear. Based on the smog chamber experiments, here we investigated the yield and formation pathway of SOA from acetone photochemical reactions under low-NOx conditions in the presence of preexisting haze particles ((NH4)2SO4 and NH4HSO4) and saline mineral particles (Na2SO4) under ammonia-rich conditions. Our results showed that the yield of acetone-derived SOA is remarkably enhanced via multiphase reactions in the presence of these preexisting seeds, especially for the saline mineral particles. We found that aerosol acidity is a key factor controlling the formation pathways of acetone-derived SOA, in which organic acids, alcohol, and carbonyls produced from acetone photochemical reactions dissolve into the aqueous phase of the preexisting seeds and subsequently esterify and/or oligomerize into SOAs that consist of larger molecules on the acidic aerosols but smaller molecules on the neutral mineral aerosols. Moreover, the light absorption ability of the acetone-derived SOA formed on (NH4)2SO4 aerosols is stronger than that formed on Na2SO4 mineral particles, especially in the presence of ammonia, due to a formation of N-containing organics. Through comparison with that from methylglyoxal (MGly), we found that the total SOA from acetone in the chamber is 2.8–8.2 times that from the irreversible uptake of MGly, suggesting that only considering MGly as the precursor of acetone-derived SOA will probably underestimate the role of acetone in global SOA production since acetone abundantly exists in the troposphere.